The International monetary system : a time of turbulence - Dreyer, Jacob S.; Haberler, Gottfried; Willett, Thomas D.; American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1982)
The book is proceedings of a conference sponsored by the American Enterprise Institute for Public Policy Research, and held Feb. 28-29, 1980, in Washington, D.C. Includes bibliographical references.
Includes bibliographical references.
usc 03/05/18
Loans
Keywords: International finance; Foreign exchange rates; Foreign exchange